Distribution and Main Influencing Factors of Net Ecosystem Carbon Exchange in Typical Vegetation Ecosystems of Southern China - Yike Wang; Xia Liu; Weijia Lan; Shuxian Yin; Liya Fan; Boru Mai; Xuejiao Deng (Aerosol and Air Quality Research)
Abstract Changes in the net ecosystem carbon exchange (NEE) significantly influence the atmospheric CO2 concentration. However, our understanding of carbon cycling in various vegetation types still needs further expansion. This study investigated the NEE characteristics of typical evergreen coniferous forest ecosystems (ECFEs), tree-and-crop mixed ecosystems (TCMEs), and coastal crop ecosystems (CCEs) in southern China. The prevailing factors that influence CO2 fluxes, including the planetary boundary layer (PBL), vapor pressure deficit (VPD), and photosynthetically active radiation (PAR), were also examined. The results showed that (1) the NEE of ECFEs was highest in winter and lowest in summer, with an annual average of –4.21 ± 0.44 μmol m-2 s-1. The NEE values of TCMEs and CCEs were comparable and significantly lowerthan that in ECFEs, with annual average NEE values of –1.96 ± 0.09 μmol m-2 s-1 and –1.98 ± 0.04 μmol m-2 s-1, respectively. ECFEs exhibited an average annual carbon capture rate of 15.93 tons C (10,000 square meters)-1 (year)-1, while TCMEs and CCEs recorded lower rates of 7.42 and 7.49 tons C (10,000 square meters)-1 (year)-1, respectively. (2) The NEE remained relatively stable during the night across all types of ecosystems. However, a noticeable minimum value occurred around noon, mainly due to a combination of heightened photosynthesis, an elevated VPD, and an increased PBL height. (3) Near the light saturation point, decreased VPD improved light utilization, shifting the minimum light use efficiency (LUE) toward lower radiation levels. However, after exceeding the light saturation point, changes in VPD had no significant effect on the LUE. (4) Compared with the vegetation in the TCME, that in the ECFE exhibited a 120.00% increase in annual ecosystem apparent quantum yield (X) and a 24.23% increase in maximum gross ecosystem exchange at light saturation (GEEmax), while the half-saturated light intensity (PAR0) decreased by 43.53%.